Compressible All‐In‐One Supercapacitor with Adjustable Output Voltage Based on Polypyrrole‐Coated Melamine Foam. (27th September 2019) - Liu, Qifan; Zang, Limin; Qiao, Xuan; Qiu, Jianhui; Wang, Xue; Hu, Lei; Yang, Jun; Yang, Chao
Abstract: Compared with laminated structure supercapacitors, all‐in‐one supercapacitors can reduce the contact resistance of the interface and avoid displacement/delamination of the multilayer structure under deformation, which suggests a highly promising energy‐storage device. However, simplifying the assembly process to achieve high voltage output, balance mechanical stability and electrochemical performance is still a serious challenge. Here, an all‐in‐one flexible supercapacitor (AFSC) is designed based on melamine foam and polypyrrole by one‐step polymerization method. It exhibits a high volumetric specific capacitance of 2.86 F cm −3, volumetric energy density of 0.18 mWh cm −3, and volumetric power density of 22.97 mW cm −3 . Moreover, it exhibits outstanding mechanical stability which can work stably under different compressive strains. More surprisingly, the output voltage of the AFSC can be adjusted handily by a simple cutting method without connecting several supercapacitors in series. The excellent performance of the device indicates that it has great potential for use in highly integrated portable and wearable electronic devices. Abstract : A compressible all‐in‐one flexible supercapacitor based on polypyrrole‐coated melamine foam that can easily extend its voltage window is fabricated. This device exhibits excellent capacitance retention under different compressive strains and can extend its voltage window without connection of additional devices in series, which is promising for use in portable and wearable electronics.